2021
DOI: 10.3390/ma14154096
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Basalt Fiber Crack Resistance of Asphalt Concrete Based on Acoustic Emission

Abstract: In this study, the semicircle three-point bending tests of ordinary asphalt concrete and basalt fiber asphalt concrete were carried out and acoustic emission parameters were collected during the test. The differences of the characteristics of acoustic emission parameters between basalt fiber asphalt concrete and ordinary asphalt concrete were analyzed, and the damage stages were divided based on the variation of acoustic emission parameters; Rise Angle and Average Frequency were introduced to study the crackin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Yang et al [ 43 ] employed the acoustic emission technique to analyze the performance of specimens in semicircular three-point bending tests and concluded that the addition of BFs may block the development of the main macroscopic crack and toughen the mixture. The rapid fracture stage is the main stage during which BFs provide crack resistance and toughening.…”
Section: Performance Of Asphalt Mixture Modified With Basalt Fibermentioning
confidence: 99%
“…Yang et al [ 43 ] employed the acoustic emission technique to analyze the performance of specimens in semicircular three-point bending tests and concluded that the addition of BFs may block the development of the main macroscopic crack and toughen the mixture. The rapid fracture stage is the main stage during which BFs provide crack resistance and toughening.…”
Section: Performance Of Asphalt Mixture Modified With Basalt Fibermentioning
confidence: 99%
“…From the above test results, it can be seen that the fracture energy of modified asphalt and base asphalt at UV160h were 0.752 and 0.483 MPa, respectively. The higher the fracture energy of the material, the better the crack resistance [51], indicating that the crack resistance of SBS-2 modified asphalt after aging was better than that of base asphalt. Comparing the results of the ductility and BBR tests, it can be concluded that the asphalt crack resistance obtained by the full-face fracture energy method correlated well with these two tests.…”
Section: Full-section Fracture Energy Testmentioning
confidence: 99%
“…Adding a small amount of fiber can significantly increase the viscosity of the asphalt mortar, hinder the effective flow of the asphalt, and, to some extent, lower the cracking probability of asphalt mortar, thus improving its low-temperature crack resistance. This provides the theoretical foundation for the popularization and application of BF in asphalt pavement [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%